Exploring Croatian In-Service Primary Teachers’ Professional Attitudes Toward Science Using the Dimensions of Attitude Toward Science (DAS) - Nataša Erceg; Tatjana Ivošević (Education Sciences)
Teachers holding positive professional attitudes towards science is a key prerequisite for high-quality teaching and consequently for the sustainability of ongoing science education reform, which is being implemented in Croatia for the first time. Therefore, this cross-sectional study examined the attitudes, views, and self-reported behaviour of primary school teachers in the context of science teaching. The sample included 950 teachers during the 2024/2025 school year. Data were collected using the DAS questionnaire and analyzed using descriptive and inferential statistical methods. Most teachers expressed positive professional attitudes toward science teaching and held, broadly defined, a contemporary view of science. However, the frequency of implementing science-specific teaching activities remained relatively low. Correlational analyses revealed a moderate positive association between attitudes and behaviour (r = 0.396, p < 0.001), and a weak but statistically significant association between attitudes and views of science (ρ = 0.081, p = 0.012). The results indicate the need for systematic support in teacher education and professional development, particularly in strengthening teachers’ competencies required for conducting science-related activities. This study contributes to a deeper understanding of teachers’ professional orientations within the context of Croatia’s current educational reform and provides a foundation for aligning national practice with European evidence-based educational policies.